Breathing free the 5-day breathing programme that will change your life - Hale, Teresa (Hodder & Stoughton, 1999)
A guide to the drug-free approach of the Buteyko Method for asthma and general health. At the heart of the method lies the recognition that some 200 diseases develop because of hyperventilation. This five-day programme provides exercises to alter your breathing patterns.